Pengenalan Coding Bagi Usia Sekolah Menggunakan Aplikasi SHINIBIK (Shinhan University dan IBI Kosgoro 1957) Bagi Murid Sekolah Dasar Negeri 11 Lenteng Agung Jakarta Selatan - Boy Firmansyah; Andri Priawijaya Nur; Filda Angelia; Waskita Cahya; Astried Silvani Akbar (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2020)
Industrial Era 4.0 brought Indonesian people to a technological mindset that covered various aspects of life. Technology is now open again to luxury things (luxury) so that people can not be separated from the rise of technological facilities. In preparation for entering the industrial era 5.0, there is no doubt that information retrieval is greatly supported and facilitated by various technology-based devices and applications. Information which is currently an important basic material in shaping concrete data makes information important in various aspects of life.Based on the adage